Computer use by secondary school principals - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Afshari, Marjan; Foo, Say Fooi; Abu Samah, Bahaman (Sakarya University, Sakarya, 2010)
The purpose of this study was firstly to identify the extent to which Iranian secondary school principals used computers and secondly to explore the relationship between a number of variables related to the use of information and communications technology (ICT). Findings indicated that four factors played a role in explaining the level of computer use by principals. These factors included high level of computer access, strong perceptions of the attributes of ICT, high level of computer competence, as well as the high level of transformational leadership behaviors, all contributed significantly to the level of computer use by principals. All four constructs are equally important but have varying impacts on computer use. Therefore, all four constructs should be viewed in an integrated manner in accordance to the conceptual model proposed in this study.